KEBERHASILAN REKLAMASI LAHAN BEKAS TAMBANG BATUBARA STUDI KASUS IZIN USAHA PERTAMBANGAN DI KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Cecep Gunawan; Badaruddin Badaruddin; Kissinger Kissinger; Hilda Susanti (EnviroScienteae, 2023)
The assessment of the success rate of reclamation uses a reference assessment of PERMENHUT 60 of 2009 with scoring of three criteria, namely: Land arrangement with a score of 30%, control of erosion and sedimentation with a score of 20%, and revegetation with a score of 50%. The reclamation success rate assessment result based on the total score is both >80, medium 60-80, and ugly <60. The implementation of reclamation of mining business permits based on the calculation of the total value obtained a value of 48.5 which shows that the reclamation results are included in the ugly criteria (reclamation results are unacceptable and intensive maintenance is needed), so it is necessary to carry out reclamation repairs. The reclamation criteria that received a less assessment was the implementation of revegetation which had the lowest value, namely, 14 out of 50 weights and erosion and sedimentation control had a value of 12 out of 20, while land management had a value of 22.5 out of a weight of 30. Activities that can be carried out to improve reclamation on former mining business permit land are land management, reducing landslides, erosion, and sedimentation, improving the quality of physical and chemical soil properties with regular fertilization and liming, spraying pesticides, cleaning cover crop windings on plants periodically carried out, reselecting cover crops, selecting sengon plants as pioneer plants, selection of jackfruit plants as local insert crops, then the commitment of policymakers in the implementation of reclamation, fulfillment of labor competencies, remaking of erosion and sedimentation control facilities, and providing facilities and infrastructure for breeding diverse plants.